2016
DOI: 10.1111/jwas.12317
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Community‐based Fish Culture System on Expenditure and Inequality: Evidence from Bangladesh

Abstract: This study investigated the impact of a Community‐based Fish Culture (CBFC) system on household expenditure and how expenditure inequality in the fish‐producing communities has changed due to involvement in the CBFC system. Six floodplains, comprising three project sites and three controls, were chosen from three river basin areas of Bangladesh; data for this study were collected for a period of 3 yr. A propensity score matching method was used to evaluate the impact of CBFC on household expenditure; while a G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The suite of production practices represented in the RFPP typology allow for continued testing and refining of innovations to further improve nutrition, equity, and environmental outcomes. The innovations emerging from RFPPs demonstrate gains or promise in enhancing management of landscape connectivity (in the Mekong Delta; Joffre et al, 2018;Nguyen et al, 2020), equity and inclusivity (in Bangladesh; Haque and Dey, 2016), and enabling adaptation in the face of changing environmental and sociopolitical conditions (in Myanmar; Dubois et al, 2019). Even for the long-standing rice field fisheries in Cambodia, innovation and research have enabled adaptation to the contemporary agricultural, ecological, and institutional context (Kim et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The suite of production practices represented in the RFPP typology allow for continued testing and refining of innovations to further improve nutrition, equity, and environmental outcomes. The innovations emerging from RFPPs demonstrate gains or promise in enhancing management of landscape connectivity (in the Mekong Delta; Joffre et al, 2018;Nguyen et al, 2020), equity and inclusivity (in Bangladesh; Haque and Dey, 2016), and enabling adaptation in the face of changing environmental and sociopolitical conditions (in Myanmar; Dubois et al, 2019). Even for the long-standing rice field fisheries in Cambodia, innovation and research have enabled adaptation to the contemporary agricultural, ecological, and institutional context (Kim et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…When managed inclusively, employment opportunities are generated and fishers gain additional fishing opportunity for up to 6 months each year (Haque and Dey, 2017). Successful examples have demonstrated that community based fisheries and aquaculture increased expenditure equality by 15% among community participants (Haque and Dey, 2016). In addition, the increased fish production bolstered fish consumption, especially for landless non-fishers (33% increase in annual per capita fish consumption) and improved household incomes from fish by a factor of 3.7 (Haque and Dey, 2017).…”
Section: Bangladeshmentioning
confidence: 99%
“…The connection between community and fishery culture goes beyond economic considerations (Haque and Dey, 2016). Fishery not only provides economic resources needed for many community members, but also serves as a source of social cohesion (Basavakumar et al, 2011).…”
Section: Connection Between Fishery Culture and Communitymentioning
confidence: 99%
“…Recently, articles related to economic aspects of aquaculture (Tokunaga et al ; Dresdner and Estay ; Huang et al ; Kumar et al ; Hernandez et al ) have been published in the Journal of the World Aquaculture Society . These have principally focused on production economics; only one addressed social welfare associated with aquaculture from the perspective of effects on income inequality (Haque and Dey ). Remaining important questions that warrant investigation may include: Which infrastructures benefit from the presence of aquaculture in a region and which do not?…”
mentioning
confidence: 99%